INCREASING COURTESY FOR EARLY CHILDHOOD USING JAVANESE LANGUAGE PICTURE STORY BOOK MEDIA - Budiastuti, Agustin; Khamidun, Khamidun (BELIA: Early Childhood Education Papers, 2019)
Courtesy is an unwritten rule that has been considered a good habit by Javanese people. At this time began to be abandoned by the Javanese people themselves. This research objective was to obtain empirical data about increase courtesy for early childhood using Javanese language picture story book. This type of research is experimental research (experimental research). The population in this study were students of kindergarten class B TK Sidoluhur II, Wonowoso Village, Karangtengah Sub-district, Demak Regency. The sampling technique used was saturated sample (totality sampling). The sample is 30 children. Data collection methods used were interviews, documentation and use of the Likert scale increase courtesy for early childhood using Javanese language picture story book. The Likert scale was previously tested so that it can be used in research, with results totaling 50 valid items. While the method of data analysis is descriptive and hypothesis testing with Paired Sample T Test. The results of this study are courtesy for children in behaving and speaking in Javanese language has increased. The way children talk and behave becomes more polite. Based on the results of the calculation of the Paired Sample T Test, it can be concluded that Ho is rejected and Ha is accepted. There was a significant increase in courtesy in early childhood after the Javanese language story book media was applied. The effectiveness of the media usage of Javanese language picture book is as big as 37.9668. This means that the Javanese language picture story book is effective in increasing early childhood courtesy.